Key Issues in the Intellectual Property Court’s Presidium Rulings - Maria Kolzdorf; Natalia Kapyrina; Nikolai Goloiad (Legal Issues in the Digital Age, 2024)
The comment reviews key positions in the rulings of the Presidium of the Russian Intellectual Property Court (IPC) issued between July and September of 2023. The Chamber hears cassation appeals against the decisions of the IPC first instance and deals primarily, but not only, with matters of registration and validity of industrial property rights. Therefore, the review predominantly covers substantive requirements for patent and trademark protection, as well as procedural issues both in the administrative adjudicating mechanism at the Patent office (Rospatent) and at the IPC itself. The current review encompasses a variety of topics related to trademark law, patent law and various procedural matters.